Assessment of the effectiveness of structural reforms in the management system repairs from the introduction of the tender system - L. I. Ostrinskaya; S. Yu. Pestova; N. G. Ostrinskaya; E. G. Ostrinskaya (Вестник СибАДИ, 2017)
The questions assess the effectiveness of the repair control mechanisms through the tender system. We construct a generalized diagram of the control system repairs and maintenance fund management model, determined by the scheme of subsystem distribution of investments in the economic object. The constructed model, is designed to distribute investment projects in the market of contractors, suppliers of construction and installation works in such a way as to achieve the performance to minimize investment risk and the cost of the project implementation.